(untitled) (Journal of Naval Architecture and Marine Engineering, 2025)
In this paper, we have studied analytically the relationship between oscillatory free stream flow and two-dimensional hydromagnetic oscillatory flows of a viscous, incompressible, and electrically conducting fluid past a porous, infinite limiting surface, as well as the temperature and magnetic fields that are associated with these flows. Both frequency-dependent effects and "long-time" effects, which call for impractically long channels to be observed in steady flow is studied with oscillating fluid. For many industrial processes, it is essential to comprehend the physics of oscillating flows of complex fluids in small channels. Many chemical and biochemical engineering operations depend on effective fluid mixing and efficient mass and energy transport. Our analysis was carried out using semi-analytical method in the neighborhood of epsilon. From the result obtained, we discovered that that variation of transient velocity are the same with those of the mean velocity. Also, the mean velocity increases when the limiting surface moves in the positive direction of the flow, whereas it decreases when it moves in the opposite direction and increase in magnetic parameter decreases the mean velocity and that the magnetic field is limited to only retardation. Other flow governing parameters were displayed using graphs and discussed accordingly. Journal of Naval Architecture and Marine Engineering, 22(2), 2025, PP. 183-197